(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Necrotic enteritis (NE) is one of the important enteric diseases in poultry caused by Clostridium perfringens which leads to considerable economic losses for poultry raisers. The present research was carried out to estimate prevalence, risk factors and to confirm molecular pattern, antimicrobial susceptibility status of Clostridium perfringens in layer flocks in Mymensingh and Gazipur districts of Bangladesh, where a total of 287 samples were collected that comprised of water (30), workers’ hand washing (30), and feed (30) as environmental pooled samples; cloacal swab (150) and post mortem sample (intestine) (47) as individual samples, and evaluated by basic (culture, biochemical test), and finally toxinotyping multiplex PCR assays. The flock-level data on potential risk factors were collected through semi-structured interviews with the farm owners and evaluated via univariable and multivariable logistic regression analyses where a p-value of <0.05 was considered as statistically significant. Overall flock-level prevalence of Clostridium perfringens was confirmed to be 6.3% (95% confidence interval [CI]: 3.8-9.7%). The occurrence of C. perfringens was found to be higher in the intestine samples (12.8%, 95% CI: 4.8- 25.7%) followed by feed (6.7%, 95% CI: 0.8-22.1%), cloacal swabs (6.0%, 95% CI: 2.8-11.1%) and workers’ hand washing (3.3%, 95% CI: 0.1- 12.2%). History of immune-suppressive disease (like New castle disease/egg drop syndrome/infectious bursal disease) [Odds Ratio (OR) = 22.16, 95% CI: 1.40-349.36, P = 0.027] and flock size more than 3000 birds (OR = 11.16, 95% CI: 1.26-98.25, P = 0.029) were found to be associated with C. perfringens infection status in the layer flocks. In this study, C. perfringens toxinotype A is circulating in layer flocks with 72.2% of isolates were established as multidrug-resistant as they demonstrated resistance between 3 to 6 antimicrobial agents. Evidence-based control measures to be taken namely use of probiotics, prebiotic, organic acids, and plant extracts as natural alternatives including control of immune-suppressive diseases are needed to minimize the NE infection and antimicrobial resistance in low biosecurity layer flocks. Asian Australas. J. Biosci. Biotechnol. 2022, 7(2), 36-49